2019
DOI: 10.1039/c8mt00278a
|View full text |Cite
|
Sign up to set email alerts
|

Induced CD of iron(ii) clathrochelates: sensing of the structural and conformational alterations of serum albumins

Abstract: Iron(ii) clathrochelates are protein-sensitive CD reporters able to discriminate proteins of similar structure (HSA and BSA) and reflect the transitions of protein conformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…Recently, it has been discovered that the binding to bovine serum albumin (BSA) makes the optically inactive iron(II) clathrochelates functionalized with carboxyphenylsulfide groups able to induce circular dichroism spectra (ICD) [25]. As an explanation to this phenomenon, we suggested that BSA binding sites are suited to predominant fixation of one of the two (Λ or ∆) trigonal prismatically (TP)-trigonal antiprismatically (TAP)-distorted conformations of the clathrochelate framework [26]. The iron(II) clathrochelate isomers with six carboxyphenylsulfide groups were reported to give a substantially different ICD response upon binding to BSA and to human serum albumin (HSA), thus allowing us to discriminate between these two structurally related proteins [26].…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Recently, it has been discovered that the binding to bovine serum albumin (BSA) makes the optically inactive iron(II) clathrochelates functionalized with carboxyphenylsulfide groups able to induce circular dichroism spectra (ICD) [25]. As an explanation to this phenomenon, we suggested that BSA binding sites are suited to predominant fixation of one of the two (Λ or ∆) trigonal prismatically (TP)-trigonal antiprismatically (TAP)-distorted conformations of the clathrochelate framework [26]. The iron(II) clathrochelate isomers with six carboxyphenylsulfide groups were reported to give a substantially different ICD response upon binding to BSA and to human serum albumin (HSA), thus allowing us to discriminate between these two structurally related proteins [26].…”
Section: Introductionmentioning
confidence: 95%
“…As an explanation to this phenomenon, we suggested that BSA binding sites are suited to predominant fixation of one of the two (Λ or ∆) trigonal prismatically (TP)-trigonal antiprismatically (TAP)-distorted conformations of the clathrochelate framework [26]. The iron(II) clathrochelate isomers with six carboxyphenylsulfide groups were reported to give a substantially different ICD response upon binding to BSA and to human serum albumin (HSA), thus allowing us to discriminate between these two structurally related proteins [26]. In addition, the clathrochelates with two carboxyphenylsulfide substituents have shown different optical responses upon their supramolecular assembly with globular proteins, permitting to distinguish between albumins and beta-lactoglobulin (BLG) [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the earlier-described d-metal monomacrobicyclic complexes (clathrochelates [1,2]) and their bis-cage analogs, shown in Scheme 1 with terminal biorelevant, first of all, carboxyl group(s), compounds 1-5 are reported to be the most prospective bioeffectors, including the so-called "topological drugs" [2,3] and molecular optical probes [4][5][6]. They possess the highest inhibitory activities in the transcription systems of T7 RNA [7,8] and Taq DNA [9] polymerases, the best antifibrillogenic properties [10] and the most intensive CD outputs on their supramolecular binding to albumins [4][5][6] as well. The latter results are explained [4][5][6] by strong supramolecular interactions of the terminal polar and/or H-donor group(s) of a given macrobicyclic "guest" with appropriate aminoacid residues of a suitable protein macromolecule as a "host" upon their non-covalent host-guest clathrochelate-protein self-assembly.…”
Section: Introductionmentioning
confidence: 99%
“…They possess the highest inhibitory activities in the transcription systems of T7 RNA [7,8] and Taq DNA [9] polymerases, the best antifibrillogenic properties [10] and the most intensive CD outputs on their supramolecular binding to albumins [4][5][6] as well. The latter results are explained [4][5][6] by strong supramolecular interactions of the terminal polar and/or H-donor group(s) of a given macrobicyclic "guest" with appropriate aminoacid residues of a suitable protein macromolecule as a "host" upon their non-covalent host-guest clathrochelate-protein self-assembly. Moreover, very recently, one of the macrobicyclic iron(II) complexes, the molecule that contains one terminal functionalizing carboxyl group, has been found [11] to possess both high in vitro cytotoxicity and selectivity (as compared with normal cells) against the human promyelocytic leukemia cell line.…”
Section: Introductionmentioning
confidence: 99%